ANALISIS PERILAKU BULLYING DI SEKOLAH UPT SDN 060874 MEDAN PERJUANGAN - Riski, Luthfiyah; Rahayu, Puji; Lubis, Via Ranzani; Utami, Tria; Sitepu, Melyani Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Bullying is an act or behavior that is intentional and persistent both individually and in groups through verbal, physical, and psychological behavior that aims to cause physical, social, and psychological harm to someone.This study aims to describe bullying behavior that occurs in students at the UPT SDN 060874 Medan Perjuangan school, this research uses descriptive qualitative methods with data collection techniques through 3 ways, namely observation, interviews, and questionnaires.The results showed that almost most of the students had experienced bullying. Bullying behavior is divided into three types, namely verbal, relational and physical bullying.Verbal bullying behavior that exists such as taunts by calling parents names, physical taunts, minority discrimination, and also taunts because of weaknesses such as stupid, smelly, yelling and cheering.Relational bullying is an action that can be felt emotionally and physically, relational bullying that occurs is playing in groups (gangs), spreading gossip or inciting, using bad body language such as glaring sarcastically, looking away, inhabiting friends (hostile), and facial expressions that demean others.Physical bullying is an action that is carried out directly against the human body, physical bullying behavior that occurs is, pulling friends' clothes and bags, damaging friends' belongings, tripping legs, crossing friends' hands and tables, pushing friends.